2018 IEEE International Conference on Communications (ICC) 2018
DOI: 10.1109/icc.2018.8422913
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for End-to-End Latency Measurements in a Satellite Network Environment

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The actual latency figures measured by experiments with a real GEO satellite and terrestrial network testbed (see Section III-B), summarized in Tables I and II [30], were used to compute numerical results by implementing the TCP and Hybla congestion control algorithms (see (1) to (9)) in a Matlab program. During algorithm implementations, an ideal channel (i.e error free with P ER = 0) was considered and in the absence of congestion for effective evaluation and analysis and better understanding.…”
Section: B Results Performance Evaluation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The actual latency figures measured by experiments with a real GEO satellite and terrestrial network testbed (see Section III-B), summarized in Tables I and II [30], were used to compute numerical results by implementing the TCP and Hybla congestion control algorithms (see (1) to (9)) in a Matlab program. During algorithm implementations, an ideal channel (i.e error free with P ER = 0) was considered and in the absence of congestion for effective evaluation and analysis and better understanding.…”
Section: B Results Performance Evaluation and Analysismentioning
confidence: 99%
“…The setup assumes a Bent-Pipe (BP) satellite hop, which doubles the latency due to intermediary gateway stations (GWS). Scenarios were developed and used to derived a framework for the measurement, details of which are published in [30].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The E2E latency measurement used for performance evaluation for different scenarios are described in [28], the setup consisted of real Wi-Fi and Satellite hybrid links connected to a Broadband Global Area Network (BGAN ). The satellite BGAN link has maximum Achievable Throughput (ATP) of 464kbps connecting three Wi-Fi nodes with two of the nodes generating TCP traffic over the link while the other node serve as TCP traffic sink.…”
Section: End-to-end Performance Evaluationmentioning
confidence: 99%
“…This variable sets limits to the amount of data the sender can transmit into the network path before an acknowledgement is received. The results obtained in this paper using Equation 3 were used to compute and evaluate E2E capacity utilisation with knowledge of the system's available capacity C The E2E latency measurement results obtained experimentally in [28] using real SatComs network environment showed that the E2E latency is much higher than assumed by many studies related to SatCom, particularly geostationary [25]- [27].…”
Section: A End-to-end Latency and Throughputmentioning
confidence: 99%
“…2) Packet Delay Variation: PDV is described as the variation in packet delay inside a given media at the mobile user station and always measured in msec. Eq.3 describes PDV for multimedia streaming procedure with ideal ranges <50 msec [17]- [19].…”
mentioning
confidence: 99%